Seroprevalence of Hepatitis a in Hemodialysis Patient Candidate for Kidney Transplant Younger Than Forty Years - Abolghasemi, Sara; Sali, Shahnaz; Arabsaghari, Ensieh; Sadeghian, Yasan; Samadian, Fariba; Alirezaie, Amirhesam; Manshouri, Shirin; Parvin, Mahmoud; Shabani, Mohammad Hassan (Novelty in Biomedicine, 2017)
Background: Hepatitis A is a common infection during childhood, especially in developing countries. It can cause severe complications in immunocompromised patients. Due to the increasing number of kidney transplants in the country and epidemiologic shift of HAV which was observed in previous studies, we’re going to evaluate the seroprevalence of hepatitis A in hemodialysis patients less than forty years serving kidney transplant candidates to follow vaccination policy for them. Materials and Methods: In a cross sectional study during 2014-2015 hepatitis A antibody levels in hemodialysis patients less than forty years in kidney transplant candidates examined in 12 hospitals in Tehran, Iran. Their serums were tested for anti HAV IgM and IgG by ELISA kits. Results: Hepatitis A virus antibody was positive in 66 (72.5%) of 91 patients. The prevalence of HAV was 0% at the range of younger than 20 and 45% in under 25 years age group. This significantly increased prevalence by increasing the age, and there was according to epidemiological shifts which were shown in other studies. Conclusion: Due to the availability of vaccine and hepatitis severe complications in immunocompromised individuals, as well as a low prevalence of positive serology in individuals under 25 years, it seems the check of antibodies in patients undergoing kidney transplantation and vaccination in seronegative persons is a logical.